Generation of Monoclonal Antibodies against Highly Conserved Antigens - Zhou, Hongzhe (Public Library of Science, 2009)
BACKGROUND: Therapeutic antibody development is one of the fastest growing areas of the pharmaceutical industry. Generating high-quality monoclonal antibodies against a given therapeutic target is very crucial for the success of the drug development. However, due to immune tolerance, some proteins that are highly conserved between mice and humans are not very immunogenic in mice, making it difficult to generate antibodies using a conventional approach. METHODOLOGY/PRINCIPAL FINDINGS: In this report, the impaired immune tolerance of NZB/W mice was exploited to generate monoclonal antibodies against highly conserved or self-antigens. Using two highly conserved human antigens (MIF and HMGB1) and one mouse self-antigen (TNF-alpha) as examples, we demonstrate here that multiple clones of high affinity, highly specific antibodies with desired biological activities can be generated, using the NZB/W mouse as the immunization host and a T cell-specific tag fused to a recombinant antigen to stimulate the immune system. CONCLUSIONS/SIGNIFICANCE: We developed an efficient and universal method for generating surrogate or therapeutic antibodies against “difficult antigens” to facilitate the development of therapeutic antibodies.